Integrated Assessment of Industrial Wastewater Treatment Using Rice Husk (Oryza Sativa) Biosorbent: A Treatment Efficiency Index Approach in Kirkuk, Iraq - Sedeeq, Ann Ahmed (American Journal of Biology and Natural Sciences, 2026)
Background and Objectives: Oil and industrial wastewaters have an high load of heavy metals and physico-chemical pollutants which are human health environmental threats. Treatments are costly and complicated, this kind of illness undertreated in the developing countries including Iraq. This research explored the application of rice husks (Oryza sativa) as an inexpensive adsorbent for industrial wastewater treatment obtained from North Oil Company, Kirkuk and applied Treatment Efficiency Index (TEI) to assess the overall efficiency. Materials and Methods: The analysis were made in wastewater samples that was collected for a number of physicochemical parameters including pH, electrical conductivity (EC), TDS, TSS, turbidity, BOD, COD and for heavy metals (Pb and Cd) before and after treatment. The husk of rice was used as a filtration bio-sorbent and the experiment conditioned in laboratory. TEI was derived using the average removal efficiency for all measured parameters to produce an overall assessment of treatment. Results: Fixed bed filter from fine rice husk powder (Oryza sativa) was used in treating the industrial effluent of North Oil Company, Iraq. The treatment resulted in better physicochemical properties such as pH (6.2 ± 0.3 to 7.1 ± 0.2), electrical conductivity (2150 ± 120 to 780 ± 95 µS/cm; removal efficiency of 63,7) and turbidity (145 ±12 to13±6 NTU; level of reduction of91since %). Dissolved O2 past from 2.1 ± 0.4 to 2.3 ± 0.5 mg/L, Total dissolved solids and total suspended solid flows went down, respectively, from 1380 ±85 to 790 ± 60 mg/L (42.8% removal) and from 420±30 to160±18 mg/L (61.9%). Organic indicators also decreased, with BOD₅ decreasing from 210 ± 20 to 85 ± 10 mg/L (59.5% removal) and COD from 460 ± 35 to 190±22 mg/L (58.7% removal). Major ions and nutrients (total hardness, alkalinity, chloride, sulphate, nitrate and phosphate) decreased by 36.5–63.2%. Heavy metals exhibited a promising removal rate: lead (from 1.85 ± 0.15 to 0.12 ± 0.06 mg/L, by approximately 93.5%) and cadmium (from 0.92 ± 0.08 to 0.09 ± 0.01 mg/L, i.e., around 90.2%). Treatment efficiency indices (TEI) were between 56.2% in the case of motor oil wastewater and 63.0% for heavy metal–spiked wastewater. Nevertheless, TSS, turbidity, BOD₅, COD-Pb and Cd concentrations were above WHO/EPA guidelines after treatment process, which should consume water from direct-drinking without other purification. Conclusions: Rice husk (Oryza sativa) emerges as a potential low-cost biosorbent for physical-chemical pollutants and heavy metals in the industrial effluents. The application of TEI provides an efficient and integrated approach to assess overall treatment performance, which will be useful in industrial areas being scarcity of resources.